2015
DOI: 10.1111/jph.12398
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Pathogenicity of Lasiodiplodia Species from Eucalyptus urophylla × grandis, Polyscias balfouriana and Bougainvillea spectabilis in Southern China

Abstract: Species of Lasiodiplodia are important pathogens of a wide variety of plants covering a wide geographical distribution. These fungi can be associated with different symptoms such as stem cankers, shoot blights, fruit rots, dieback and gummosis. Diseases caused by Lasiodiplodia were surveyed on Eucalyptus urophylla 9 grandis, Polyscias balfouriana and Bougainvillea spectabilis in a nursery in southern China. Based on morphology characteristics and phylogenetic analyses of ITS rDNA sequences and translation elon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…Relatively little research has been conducted on diseases caused by Botryosphaeriaceae on Eucalyptus trees in China ( Chen et al 2011c , Li et al 2015a ). Based on DNA sequence comparisons and morphological features, five species of Botryosphaeriaceae have been identified from Eucalyptus in China to date, including Botryosphaeria fabicerciana from FuJian, GuangXi and HaiNan Provinces, Lasiodiplodia pseudotheobromae from GuangXi Province, L. theobromae from GuangDong and GuangXi Provinces, Neofusicoccum parvum from FuJian and GuangXi Provinces and N. ribis s.lat.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Relatively little research has been conducted on diseases caused by Botryosphaeriaceae on Eucalyptus trees in China ( Chen et al 2011c , Li et al 2015a ). Based on DNA sequence comparisons and morphological features, five species of Botryosphaeriaceae have been identified from Eucalyptus in China to date, including Botryosphaeria fabicerciana from FuJian, GuangXi and HaiNan Provinces, Lasiodiplodia pseudotheobromae from GuangXi Province, L. theobromae from GuangDong and GuangXi Provinces, Neofusicoccum parvum from FuJian and GuangXi Provinces and N. ribis s.lat.…”
Section: Introductionmentioning
confidence: 99%
“…Based on DNA sequence comparisons and morphological features, five species of Botryosphaeriaceae have been identified from Eucalyptus in China to date, including Botryosphaeria fabicerciana from FuJian, GuangXi and HaiNan Provinces, Lasiodiplodia pseudotheobromae from GuangXi Province, L. theobromae from GuangDong and GuangXi Provinces, Neofusicoccum parvum from FuJian and GuangXi Provinces and N. ribis s.lat. from FuJian Province ( Chen et al 2011c , Li et al 2015a ). These species were collected from cankered stems and blighted branches or twigs, and pathogenicity tests showed that all five species could produce lesions on Eucalyptus seedlings or trees ( Chen et al 2011c , Li et al 2015a ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Abdollahzadeh et al, 2010). This fungus was also found in Bougainvillea spectabilis in China (Li et al, 2015), Adansonia digitata in Benin, Cameroon, Madagascar, Mozambique, Senegal and South Africa (Cruywagen et al, 2017), among others. In Brazil, this species was one of the most prevalent in the northeastern region, associated with stem-end rot on mango trees (Marques et al, 2013a), and it was reported causing dieback on Anacardium sp.…”
Section: Discussionmentioning
confidence: 84%